Reinvigorating Islamic Renaissance through Tamshiyyah al-Muslimīn: A Content Analysis Approach - Nur'aeni, Ulvah (QOF, 2024)
This study explored the concept of Islamic revival proposed by KH. Ahmad Sanusi, a traditional Islamic scholar, in his Quranic exegesis Tamshiyyah al-Muslimīn in the early 20th century. Moreover, this research investigated the narratives of Islamic revival, and the decline of Muslims explained in the exegesis. The study employed a qualitative approach based on library research to achieve its objectives. Additionally, content analysis was utilized to enhance the depth of the research analysis.  The findings reveal that Sanusi's Islamic revival concept is rooted in the Qur’an, social life, and spirituality. Regarding the Qur’an, Sanusi emphasized the importance of understanding the Quran as a source of guidance for Muslims in all aspects of life. He criticized both traditional and modernist scholars for their misinterpretation of the Quran. Concerning social life, Sanusi highlighted the significance of mastering various fields of knowledge, promoting unity among Muslims, and engaging in deliberation based on equality. In terms of spirituality, Sanusi responded to the Sufi concepts and practices that some scholars considered deviant at that time. He argued that Sufism did not hinder Muslims from achieving progress in life. Sanusi's thoughts on Sufism were influenced by al-Ghazali's concepts, which were widely spread in the Indonesian Muslim community. This study contributes to the understanding of Islamic revival from the perspective of a traditional scholar who accommodates local culture and traditions without compromising the fundamental message of Islam.